Design of a Horizontal Transfer Mechanism Between Wheelchair and Car for Disabled - Abdullah, Muhammad Faaez Amiruddin; Tee, Kian Sek (Evolution in Electrical and Electronic Engineering, 2024)
This work addresses a significant issue faced by wheelchair-dependent individuals, particularly those using the Perodua Myvi model, who often require assistance for car transfers. The proposed Wheelchair Transferring System aims to alleviate the challenges associated with these transfers, considering that one in three carers may experience back pain due to the strain of lifting objects. The system has been tested successfully, demonstrating functionality and capacity for handling weights up to 100 kg. Focused on the Perodua Myvi model, the primary goal of this work is to enhance the safety and efficiency of wheelchair users’ transfers, while also reducing physical strain on carers. The achieved results align well with the objectives, marking significant progress in improving accessibility and overall well-being for people with disabilities and their carers.